2017
DOI: 10.4314/jasem.v21i1.4
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of physicochemical parameters and some trace metals at the disposal points of five industrial effluents in Trans-Amadi Industrial Area of Port Harcourt, Nigeria

Abstract: Industrial effluent samples collected from the disposal point of five different companies in Trans-Amadi industrial area of Port Harcourt were analyzed to investigate effect on the environment. The analyzed effluent samples showed results of the physicochemical parameters and trace metals in the ranges : (pH 3.60 -6.90), electrical conductivity (406

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 13 publications
(14 reference statements)
1
7
0
Order By: Relevance
“…Ma [21] equally stated that the tolerance limit of PH varies from 6 to 9 for wastewater. Likewise, Chikwe and Onojake [29] concurred with the values given by Ma [21] for industrial effluents. Sathya [22] reported that Ravindra etal.…”
Section: Key Effluent Parameters For Gas Turbine Engine Monitoringsupporting
confidence: 76%
See 3 more Smart Citations
“…Ma [21] equally stated that the tolerance limit of PH varies from 6 to 9 for wastewater. Likewise, Chikwe and Onojake [29] concurred with the values given by Ma [21] for industrial effluents. Sathya [22] reported that Ravindra etal.…”
Section: Key Effluent Parameters For Gas Turbine Engine Monitoringsupporting
confidence: 76%
“…Ph: According to Ma [21], PH, or potential hydrogen refers to its H + activity and it is given as the log of the reciprocal of H+ activity at a given temperature. Chikwe and Onojake [29] stated that the PH is a numeric scale used to specify the acidity or basicity of an aqueous solution. Chikwe and Onojake [29] further reported that Aina etal.…”
Section: Key Effluent Parameters For Gas Turbine Engine Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum percent reduction of total solids (99.99%) was at par at 20% (0.14 mg/l), 40% (0.10 mg/l), 60% (0.06 mg/l) and 80% UDE (0.66 mg/l), and 100% UDE (0.14 mg/l) (Table 2). TSS quality checks the wastewater after treatment in the plant and is defined as the dry weight of particles trapped by a filter (Chikwe and Onojake, 2016). UDE is characterized by higher levels of TDS, which is contributed by a higher concentration of biodegradable organic matter (Kotteswari et al, 2012).…”
Section: Environment Conservation Journalmentioning
confidence: 99%